Factors Affecting Gen Z Customers’ Satisfaction with Sales Promotions of Vietnam E-Commerce Platforms - Thuy, Dao Cam; Lien, Nguyen Thi; My, Dang Pham Y (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
The complicated epidemic situation has made e-commerce platforms grow vigorously because the demand for purchasing on the Internet is increasing day by day. In this paper, the authors aim to determine the factors affecting the satisfaction of Gen Z customers with the promotional programs of e-commerce platforms in Vietnam. Data was collected from 334 Gen Z customers. The analysis results show that there are three factors affecting service quality including security, responsiveness, and payment. Furthermore, these factors have an influence on customer satisfaction as well. Based on the research results, the authors also offer some recommendations for improving the quality of e-commerce platforms and increasing their competitiveness in the current context.